Quantifying Binding of Ethylene Oxide-Propylene Oxide Block Copolymers with Lipid Bilayers - Zhang, Wenjia (Langmuir : the ACS journal of surfaces and colloids, 2017)
Block copolymers composed of poly(ethylene oxide) (PEO) and poly(propylene oxide) (PPO) have been widely used in cell membrane stabilization and permeabilization. To explore the mechanism of interaction between PPO-PEO block copolymers and lipid membranes, we have investigated how polymer structure influences the polymer-lipid bilayer association by varying the overall molecular weight, the hydrophobic and hydrophilic block lengths, and the end-group structure systematically, using 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) unilamellar liposomes as model membranes. Pulsed-field-gradient NMR (PFG-NMR) was employed to probe polymer diffusion in the absence and presence of liposomes. The echo decay curves of free polymers in the absence of liposomes are single exponentials, indicative of simple translational diffusion, while in the presence of liposomes, the decays are biexponential, with the slower decay corresponding to polymers bound to liposomes. The binding percentage of polymer to the liposome was quantified by fitting the echo decay curves to a biexponential model. The NMR experiments show that increasing the total molecular weight and hydrophobicity of the polymer can significantly enhance the polymer-lipid bilayer association, as the binding percentage and liposome surface coverage both increase. We hypothesize that the hydrophobic PPO block inserts into the lipid bilayer due to the fact that little molecular exchange between bound and free polymers occurs on the time scale of the diffusion experiments. Additionally, as polymer concentration increases, the liposome surface coverage increases and approaches a limit. These results demonstrate that PFG-NMR is a simple yet powerful method to quantify interactions between polymers and lipid bilayers